Recent Trends in Biotechnology and Therapeutic Applications of Medicinal Plants - Shahid, Mohd.; Shahzad, Anwar.; Malik, Abida.; Sahai, Aastha. (Springer Netherlands : Imprint: Springer, 2013)
The necessity of safe and cost effective medication especially for under developed and developing regions of the world together with emergence of new chronic and drug resistant diseases have prompted scientists to look towards medicinal plants as agents for treatment and prevention. This book provides an overview of advances and recent trends in medicinal plant sciences along with biotechnological interventions that has made it increasingly feasible to exploit these natural resources and transform traditional medicines into modern drugs. The book starts with a chapter discussing different types of phytoactive compounds which are the elementary substances behind medicinal action of plant extracts. Thereafter different biotechnological tools and techniques like bioreactors, hairy root culture and elicitation which are utilized to enhance and tap these valuable compounds at commercial level, are discussed in detail. The publication provides state-of-the-art information on the recent trends and technologies in medicinal plant science. The novel approaches of using plants as a source for neutraceuticals and vaccines have been thoroughly discussed in light of ongoing advancements. This work also features a compilation of standardized in vitro conservation protocols for some commercially important, rare, threatened and endangered medicinal plants. The book includes work from researchers on antimicrobial activity of various plants species native to different geographical regions around the globe. The book provides an essential text for advanced students, teachers, and research scientists in the fields of pharmacy, medical sciences, plant biotechnology, phytochemistry, and plant tissue culture.